TINDAK TUTUR EKSPRESIF DALAM FILM MIRACLE IN CELL NO. 7 VERSI INDONESIA KARYA HANUNG BRAMANTYO - Jesika, Jesika; Syam, Christanto; Syahrani, Agus (Universitas Tanjungpura, 2025)
This research focuses on analyzing the forms of expressive speech acts in the movie titled